(untitled) (2014)
HaviStat© v2.2 is available in Spanish and English. In this version reported errors and recommendations from v1.0 were fixed and implemented. HaviStat© allows users to perform the necessary mathematical, statistical and graphical procedures required to preliminarily infer use, selection, and preference for habitat/resources, and to estimate the niche breadth of species. In this new version radial diagrams, 22 indexes and 3 confidence intervals for animal preference evaluation, and 8 indexes for niche breadth estimation are available.